Magnetic properties of synthetic eumelanin - Preliminary results - Cano, M. E.; Castaneda-Priego, R.; Gil-Villegas, A.; Sosa, M. A.; Schio, P.; de Oliveira, A. J. A.; Chen, F.; Baffa, O.; Graeff, Carlos Frederico de Oliveira [UNESP] (Amer Soc Photobiology, 2008)
We report an experimental and theoretical study of magnetic properties of synthetic eumelanin. The magnetization curves are determined by using both a vibrating sample magnetometer and a superconducting quantum interferometer device in an extended range of magnetic fields ranging from -10 kOe to 10 kOe at different temperatures. We find that the eumelanin magnetization can be qualitatively explained in terms of a simple model of dipolar spheres with an intrinsic magnetic moment. The latter one is experimentally measured by using X-band electron paramagnetic resonance. Our findings indicate that synthetic melanins are superparamagnetic.